2014
DOI: 10.1016/j.bcp.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Altered matrix metalloproteinase-2 and -9 expression/activity links placental ischemia and anti-angiogenic sFlt-1 to uteroplacental and vascular remodeling and collagen deposition in hypertensive pregnancy

Abstract: Preeclampsia is a complication of pregnancy manifested as maternal hypertension and often fetal growth restriction. Placental ischemia could be an initiating event, but the linking mechanisms leading to hypertension and growth restriction are unclear. We have shown an upregulation of matrix metalloproteinases (MMPs) during normal pregnancy (Norm-Preg). To test the role of MMPs in hypertensive-pregnancy (HTN-Preg), maternal and fetal parameters, MMPs expression, activity and distribution, and collagen and elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
103
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 73 publications
18
103
1
1
Order By: Relevance
“…A study has shown that both serum MMP-2 and TIMP-1 levels are increased in PE [67], while other studies suggest that decreased levels of MMP-2 in UCA reduce the breakdown of collagen in the arterial wall [2]. Other studies have shown changes in MMP-2 and −9 protein amount and activity in uterine, placental and aortic tissue of RUPP rats [68]. MMPs may have a bi-directional relationship with VEGF, whereby VEGF upregulates MMP expression, while membrane type-1 MMP promotes VEGF expression [2].…”
Section: Extracellular Matrix and Matrix Metalloproteinases In Pementioning
confidence: 99%
“…A study has shown that both serum MMP-2 and TIMP-1 levels are increased in PE [67], while other studies suggest that decreased levels of MMP-2 in UCA reduce the breakdown of collagen in the arterial wall [2]. Other studies have shown changes in MMP-2 and −9 protein amount and activity in uterine, placental and aortic tissue of RUPP rats [68]. MMPs may have a bi-directional relationship with VEGF, whereby VEGF upregulates MMP expression, while membrane type-1 MMP promotes VEGF expression [2].…”
Section: Extracellular Matrix and Matrix Metalloproteinases In Pementioning
confidence: 99%
“…Images of the aorta, carotid artery, mesenteric artery, and renal artery were acquired using bright-field and ϫ40 objectives, and images of the virgin uterus were acquired with a ϫ4 objective. Because the rat pregnant uterus is large, 20 picture frames of sequential parts of the uterine wall were acquired using the ϫ4 objective, and the composite image of the whole uterine section was reconstituted as previously described (39). Images were analyzed using ImageJ, the total number of pixels in the tissue section image was defined, and the number of brown spots (pixels) was counted and then presented as a percentage of total pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Images of arteries were acquired using bright-field and ϫ4 and ϫ40 objectives. Because the rat uterus is large, 20 picture frames of sequential parts of the uterine tissue section were acquired using the ϫ4 objective, and the composite image of the whole uterine section was reconstituted as previously described (39). Images of tissue sections were analyzed using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…MMP-2 degrades collagen I, II, III, IV, V, VII, X and XI while MMP-9 degrades collagen IV, V, VII, X and XIV. With low MMP levels, excessive collagen deposition may affect smooth muscle growth and decrease spiral arteries remodeling [77]. …”
Section: Introductionmentioning
confidence: 99%